Critérios racionais que orientem a prescrição farmacêutica de medicamentos isentos de prescrição - Martins, Leonardo de Paula (2019)
Introduction: The Federal Council of Pharmacy (CFF) has regulated the pharmaceutical prescription in Brazil of medicines whose dispensation does not require medical prescription. However, despite the safety described in the use of OTC, there are concerns about the irrational use of these drugs. Objective: To establish and validate rational criteria based on scientific evidence that guide the pharmaceutical prescription of OTC. Methods: The research was divided into three stages. In the first, a focus group was conducted to identify which drugs would be used to create rational criteria. In the second stage, a review of the scientific literature on the drugs defined in the first stage was carried out to select information that could support the creation of rational criteria for the prescription of these drugs. In the third step, the criteria created using the Delphi Method were validated. Results: five groups of therapeutic indications and 15 drugs belonging to these groups were selected in the focal group. Of the drugs selected, one was not an OTC and for two, no relevant information was found to support the definition of rational criteria. Then, from the literature review, 12 rational criteria were created and validated using the Delphi method. Conclusion: in this validation, the lowest degree of relevance obtained for the established rational criteria was 73% and the highest of 90%. It should be noted that this thesis allowed to create and validate rational criteria for the prescription of the selected drugs and to establish a method that would achieve this objective. Other researchers are expected to use the method developed to establish new criteria. Thus, from a larger set of defined criteria, for example, an application can be developed that can aid pharmaceutical prescription and promote the rational use of medicines.